Religious and Spiritual Struggles and Mental Health Outcomes in Puerto Rico - González-Rivera, Juan Aníbal (2025)
Introduction: Religious and spiritual struggles (RSS) are psychological conflicts related to an individuals relationship with the divine, supernatural entities, or religious beliefs and communities. These struggles can cause emotional distress and negatively impact mental health. Objective: This study aimed to examine the relationship between different dimensions of RSS and mental health indicators among adults residing in Puerto Rico. Method: A correlational design was used with a convenience sample of 250 adult participants. Validated instruments were administered to assess religious and spiritual struggles, depression, anxiety, and flourishing. Results: Regression analyses showed that divine and demonic struggles significantly predicted levels of depression and anxiety, while RSS did not significantly relate to flourishing. Divine struggles emerged as the strongest predictor in both models. Conclusions: RSS, particularly those involving supernatural dimensions, are significantly associated with affective symptoms. These findings highlight the importance of addressing the spiritual dimension in clinical assessment and intervention, especially in culturally religious contexts such as Puerto Rico.